Arsenic atomic layer doping in Si using AsH3. (August 2015) - Yamamoto, Yuji; Kurps, Rainer; Murota, Junichi; Tillack, Bernd
Abstract: Atomic layer doping of arsenic (As-ALD) in Si is investigated using a single wafer reduced pressure chemical vapor deposition tool. Hydrogen-free and hydrogen-terminated Si surfaces are exposed to AsH3 in the temperature range between 300 °C and 700 °C followed by Si capping using H2 –SiH4 or H2 –Si2 H6 gas mixture at 450–700 °C. After exposing to AsH3 below 400 °C, no As spike formation is observed on both hydrogen-free and hydrogen-terminated Si surface. The incorporated As dose is increasing with increasing AsH3 exposure time and saturates. Before saturation, a higher As dose is observed at higher AsH3 partial pressure for the same AsH3 exposure time. As incorporation is not influenced by the precursor (SiH4 or Si2 H6 ) used for Si buffer deposition. By increasing SiH4 or Si2 H6 partial pressure, a higher amount of As is incorporated at AsH3 exposed surface and a higher background doping of segregated As in the Si cap is observed. The slope of the segregated As is not influenced by the growth rate at 600 °C, which means that the As segregation seems to be under thermal equilibrium. Lower segregation of As in the Si cap is observed at lower Si cap growth temperature. The results shown here may offer a precise location and dose control of As into Si.